In vitro ruminal fermentation and cow-to-mouse fecal transplantations verify the inter-relationship of microbiome and metabolome biomarkers: potential to promote health in dairy cows - Hsieh, Jui-Chun; Chuang, Shih-Te; Hsu, Yu-Ting; Ho, Shang-Tse; Li, Kuan-Yi; Chou, Shih-Hsuan; Chen, Ming-Ju (Frontiers in Veterinary Science, 2023)
There are differences in the gut microbiome and metabolome when the host undergoes different physical or pathological conditions. However, the inter-relationship of microbiome and metabolome biomarkers to potentially promote the health of dairy cows needs to be studied.Further, the development of next-generation probiotics for dairy cattle health promotion has not been demonstrated. Thus, in the present study, we identified the microbiome and metabolome biomarkers associated with healthy cows by analyzing the relationships between the ruminal microorganism profile, metabolites, and mastitis outcomes of lactating dairy cows. Two species, Ruminococcus flavefaciens and Bifidobacterium longum subsp. longum, and six rumen metabolites were positively correlated with healthy cows by Spearman's correlation analysis.Through in vitro ruminal fermentation, inoculating R. flavefaciens and B. longum subsp. longum showed the upregulation of the levels of putrescine, xanthurenic acid, and pyridoxal in the mastitis ruminal fluid, which confirmed the inter-relationships between these microbiota and metabolites associated with healthy cows. Further, we verified the role of R. flavefaciens and B. longum subsp. longum in promoting health using cow-to-mouse fecal microbiota transplantation (FMT). The administration of R. flavefaciens and B. longum subsp. longum reduced the death rate and recovered the bodyweight loss of germ-free mice caused by FMT mastitis feces. We provided evidence that the bacterial biomarkers alter downstream metabolites. This could indirectly indicate that the two bacterial biomarkers have the potential to be used as next-generation probiotics for dairy cattle, although it needs more evidence to support our hypothesis. Two species, R. flavefaciens and B. longum subsp. longum, with three metabolites, putrescine, xanthurenic acid, and pyridoxal, identified in the ruminal fluid, may point to a new health-promoting and disease-preventing approach for dairy cattle.